Comparative analysis of mechanical behavior of 3D woven spacer sandwich composites with single and double level structures. Issue 11 (20th August 2020) - Neje, Ghanshyam; Behera, Bijoya Kumar
Abstract: 3D woven spacer fabrics connected with woven cross‐links and forming tunnels of trapezoidal shape were produced in single and double level configuration with four different cell wall opening angles in each configuration. The sandwich composites produced from these spacer fabrics were then analyzed for their out‐of‐plane compressive and flexural properties to study their failure loads, energy absorbency, and failure modes. With an increase in the cell wall opening angles, compressive load and specific compressive load increased for single and double level structures, but the same properties were found to be poor for double level structures compared to their single level counterparts. Absorbed energy/volume was also found to be lower for double level composites. The bending load and specific bending load values increased with increase in cell wall opening angle, with double level structures performing better at each cell wall opening compared to their single level counterparts. But the flexural stress of double level structures was lower than that of their corresponding single level structures. The outcomes of this study can be used in designing and manufacturing of multilevel spacer structures with different cell geometrical parameters for specific end use requirements.